2004
DOI: 10.1111/j.0953-816x.2004.03356.x
|View full text |Cite
|
Sign up to set email alerts
|

Habenula lesions cause impaired cognitive performance in rats: implications for schizophrenia

Abstract: Cognitive impairment is a prominent feature of schizophrenia. Currently there is no well-accepted explanation of the aetiology of this disorder, but recent evidence indicates that dysfunction of the habenula may be involved. We therefore examined whether habenula lesions in Sprague-Dawley rats cause behavioural changes resembling those of schizophrenia. Rats received either habenula lesions, a sham operation or a small lesion of the overlying dorsal hippocampus as a check that effects observed were not due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
112
0
3

Year Published

2004
2004
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 140 publications
(121 citation statements)
references
References 96 publications
(102 reference statements)
6
112
0
3
Order By: Relevance
“…Recently, we began to examine this prediction by investigating the effects of habenula lesions on functions that are impaired in schizophrenia, namely memory performance, prepulse inhibition (PPI), and social interaction. Our results showed that habenula-lesioned rats exhibited a deficit in spatial learning in the Morris water maze, but no change of PPI or of social exploration, implicating habenula pathology particularly in memory impairment (Lecourtier et al, 2004).…”
Section: Introductionmentioning
confidence: 52%
See 4 more Smart Citations
“…Recently, we began to examine this prediction by investigating the effects of habenula lesions on functions that are impaired in schizophrenia, namely memory performance, prepulse inhibition (PPI), and social interaction. Our results showed that habenula-lesioned rats exhibited a deficit in spatial learning in the Morris water maze, but no change of PPI or of social exploration, implicating habenula pathology particularly in memory impairment (Lecourtier et al, 2004).…”
Section: Introductionmentioning
confidence: 52%
“…Instead, the stimulus recesses themselves that have become associated with reward during training elicit an inappropriate level of responding. As only a slight, short-lasting increase of locomotor activity is present in habenula-lesioned animals (Lecourtier et al, 2004), it is unlikely that the increase of premature responding is merely a reflection of generalized hyperactivity. Moreover, it seems unlikely that the increased premature responding could be explained by a motor effect of the lesion to nonspecifically facilitate responding in the stimulus alcoves, since there was no increase at all of perseverative responding caused by the lesion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations